Performing Cosmology: Sound, Movement, and World-Making in the Turuk Lagai Ritual of Mentawai - Loravianti, Susas Rita; Alfalah, Alfalah; Iswandi, Iswandi; Emri, Emri; Chaterji, Katia; Y, Eva (Resital: Jurnal Seni Pertunjukan, 2025)
This research investigates Turuk Lagai, a central ritual of the Mentawai people in West Sumatra, Indonesia, as a performative act that enacts and sustains their cosmological worldview. The study's objective is to understand how this ritual reflects belief and constitutes reality through embodied and relational practices. Using a qualitative ethnographic approach, the study draws on long-term fieldwork, in-depth interviews, and thematic analysis assisted by QualCoder. Data were coded and interpreted through a theoretical framework combining Victor Turner's ritual process, Catherine Bell's ritualization theory, and Tim Ingold's concept of relational ontology. The analysis identified three overarching themes—Embodiment, Spiritual Correspondence, and Relational Ontology—that demonstrate how bodily movement, chants, offerings, and environmental elements co-produce a cosmological order. Rather than symbolizing cosmology, Turuk Lagai brings it into being, renewing social and spiritual relationships between humans, nature, and ancestral forces. The study concludes that Turuk Lagai is a dynamic system of knowledge production and cosmological maintenance. It recommends greater recognition of indigenous ritual not as static tradition but as an active and vital mode of world-making with implications for cultural preservation and ecological ethics.